Temporal and Spatial Distribution of Organic Matter in Sudden Water Pollution Accident of Dongzhuang Reservoir - HE Cuiling; GUO Ying; CAI Dandan; LIU Shaobin; LI Guodong (Renmin Zhujiang)
Dongzhuang Reservoir is a key project of the water resource allocation network in the Weibei area in central Shaanxi.There are many industrial enterprises distributed on both sides of the reservoir area.Once a sudden water pollution accident occurs,the safety of the reservoir's water quality will be seriously threatened.In view of the possible sudden water pollution accident in Dongzhuang Reservoir,this paper,based on the MIKE 11 hydrodynamic-ECO lab module,numerically simulates the diffusion of CODMn,an organic matter,after the sudden water pollution accident in Dongzhuang Reservoir.The results show that the upstream water inflow has an obvious effect on the temporal and spatial distribution law of pollutants,and the discharge flow and discharge time of pollutants have a slight influence on the pollution zone.The influence time and influence distance of the pollution zone are controlled by changing the upstream water inflow.The results can provide a reference for formulating emergency control strategies and schemes for sudden water pollution accidents in Dongzhuang Reservoir.